A practical comparison of quantum and classical leaderless consensus - GRIFFIN, Paul Robert (Institutional Knowledge at Singapore Management University, 2022)
Quantum computing is coming of age and being explored in many business areas for either solving difficult problems or improving business processes. Distributed ledger technology (DLT) is now embedded in many businesses and continues to mature. Consensus, at the heart of DLTs, has practical scaling issues and, as we move into needing bigger datasets, bigger networks and more security, the problem is ever increasing. Consensus agreement is a non-deterministic problem which is a good match to quantum computers due to the probabilistic nature of quantum phenomena. In this paper, we show that quantum nodes entangled in a variety of network topologies perform similarly to classical consensus executed on quantum simulators and real quantum computers with and without noise mitigation. There is no difference in the average time for the network to agree but there is a higher variation in agreement times for quantum compared to classical systems. The implication is that, with continued improvement in quantum technology, the scale and advantages of quantum processing can be exploited to provide for bigger and more sophisticated consensus. Furthermore, exploring the variation in agreement time could potentially lead to shorter consensus times.